A low-cost micro-alloyed high-performance rapid-extrusion magnesium alloy and a preparation method thereof

CN117904505BActive Publication Date: 2026-10-09JILIN UNIVERSITY
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202410248809.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-03-05
Publication Date
2026-10-09
Estimated Expiration
2044-03-05

AI Technical Summary

Technical Problem

由此可见,上述AZ91合金的屈服强度可以达到200MPa以上,但合金中合金化元素含量高(>10wt.%),铸造合金中存在大量金属间化合物,且需进行长时间的均质化处理,工艺复杂;另外,合金挤压速度较慢,生产效率较低,增加生产成本,不利于镁合金的大规模工程化应用

Benefits of technology

[0009] Compared with the prior art, the present invention has the following characteristics:

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The application provides a low-cost micro-alloyed high-performance rapid extrusion magnesium alloy and a preparation method thereof, and belongs to the field of metal material processing.The magnesium alloy composition is as follows in terms of mass percentage: Bi: 0.4-2.2 wt.%, Mn: 0.3-0.7 wt.%, Zn: 0.2-0.6 wt.%, Al: 0.2-0.5 wt.%, and the rest is magnesium and inevitable impurities, and the content of the inevitable impurities is less than or equal to 0.05 wt.%. The total content of alloying elements in the alloy system is less than or equal to 4 wt.%, and the alloy system belongs to a low-alloy system. The preparation method of the alloy mainly comprises the following steps: casting a refined magnesium alloy, and then extruding the magnesium alloy into a rod. The application saves raw material production cost, simplifies a long-time high-temperature heat treatment process, can produce fine-grain strengthening and second-phase strengthening, and obtains an alloy with high strength and high elongation, wherein the yield strength is greater than or equal to 253 MPa, the tensile strength is greater than or equal to 290 MPa, and the elongation is greater than or equal to 11%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of metal material processing, specifically relating to a low-cost microalloyed high-performance rapid extrusion magnesium alloy and its preparation method. Background Technology

[0002] Magnesium alloys, as the lightest metallic structural materials, possess advantages such as low density, high specific strength and specific stiffness, good damping and vibration reduction, good machinability, and easy recycling. They are hailed as "green materials of the 21st century" and play a vital role in aerospace, automotive, rail transportation, 3C products, and medical devices. However, existing commercial magnesium alloys have relatively low absolute strength, making it difficult to meet the service requirements of structural components in automobiles and rail transportation. Adding a large amount of alloying elements (including rare earth elements) can usually effectively improve the strength of magnesium alloys through grain refinement and second-phase strengthening. For example, Dong et al. reported in their article "Difference in extrusion temperaturedependences of microstructure and mechanical properties between extruded AZ61 and AZ91 alloys" published in the Journal of Magnesium and Alloys, Vol. 11, pp. 1683-1696, 2023: Cast AZ61 and AZ91 alloys contain a large amount of intermetallic compounds. After solution treatment at 420℃ for 20 hours, the two alloys were hot extruded. The yield strengths of the extruded AZ61 and AZ91 magnesium alloys at 300℃ were 183 MPa and 232 MPa, respectively, and the yield strengths at 400℃ were 197 MPa and 224 MPa, respectively, with an extrusion speed of 1.5 m / min. Similarly, in 2020, Aria Afsharnaderi et al. published an article titled "Enhanced mechanical properties of as-cast AZ91 magnesium alloy by combined RE-Sr addition and hot extrusion" in Materials Science & Engineering A, Volume 792, pp. 644-647, which disclosed a method for preparing a magnesium alloy: by optimizing the AZ91 alloy with the addition of rare earth elements, a large number of intermetallic compounds were distributed on the grain boundaries of the alloy ingot (Al: 9wt.%, Sr: 0.1wt.%, Zn: 1wt.%, Ce: 1wt.%). First, a step solution treatment was performed (holding at 270℃ for 2h, followed by homogenization at 415℃ for 18h) to dissolve the intermetallic compounds into the matrix. Then, hot extrusion was performed at 335℃, and the yield strength of the extruded alloy was 234MPa. It can be seen that the yield strength of the AZ91 alloy can reach more than 200 MPa, but the alloy has a high content of alloying elements (>10 wt.%), a large number of intermetallic compounds in the casting alloy, and a long-term homogenization process is required, which is complicated. In addition, the alloy extrusion speed is slow, the production efficiency is low, the production cost is increased, which is not conducive to the large-scale engineering application of magnesium alloys.It should be noted that although the alloying element content of the above alloys exceeds 10 wt.%, their yield strength is still below 250 MPa, which limits the application range of magnesium alloys to some extent. Therefore, developing a low-cost, microalloyed, high-performance, rapid extrusion magnesium alloy with no rare earth elements, low alloying element content, and simple production process has become an urgent technical challenge to be solved. Summary of the Invention

[0003] To address the aforementioned technical challenges, this invention provides a low-cost, micro-alloyed, high-performance, rapidly extruded magnesium alloy. The alloy, by mass percentage, comprises the following components: bismuth: 0.4-2.2 wt.%, manganese: 0.3-0.7 wt.%, zinc: 0.2-0.6 wt.%, aluminum: 0.2-0.5 wt.%, unavoidable impurities ≤ 0.05%, and the balance being magnesium. The total content of the alloy components is ≤ 4%.

[0004] The preparation method of the magnesium alloy includes the following steps:

[0005] (1) According to the alloy composition ratio, under the protection of a mixed gas of CO2 and SF6 with a volume ratio of 95-99:5-1, pure magnesium, magnesium-manganese master alloy, pure bismuth, pure zinc and pure aluminum are melted in sequence at 500-690℃. After the alloy is completely melted, it is stirred and slag is removed for 5-20 minutes. Argon gas is introduced and the mixture is kept at a constant temperature for 15-30 minutes to obtain the alloy melt. The alloy melt is then injected into a mold preheated to 150-250℃ using gravity casting to obtain a magnesium alloy ingot.

[0006] (2) The alloy ingot obtained in step (1) is machined to obtain magnesium alloy billet;

[0007] (3) Hot extrusion: The billet and extrusion die obtained in step (2) are preheated at 300-310℃ for 2-3 hours, and then the billet is extruded at 300-310℃. The extrusion speed is 4-5m / min and the extrusion ratio is 26-30:1 to obtain a low-cost microalloyed high-performance fast extruded magnesium alloy with a yield strength ≥253MPa, tensile strength ≥290MPa and elongation ≥11%.

[0008] Further, the composition includes bismuth: 0.45-2.1 wt.%, manganese: 0.35-0.65 wt.%, zinc: 0.25-0.55 wt.%, and aluminum: 0.35-0.45 wt.%.

[0009] Compared with the prior art, the present invention has the following characteristics:

[0010] This invention achieves multiple strengthening effects, including grain refinement and second-phase strengthening, through innovative alloy composition design and synergistic control via thermo-mechanical coupling processing. The resulting extruded alloy microstructure exhibits a weak texture, which facilitates non-basal plane slip opening during plastic deformation, significantly improving alloy plasticity. Therefore, the alloy prepared by this invention exhibits good strength and plasticity. This invention uses fewer alloying elements, has lower content, and uses easily recyclable raw materials, significantly reducing material production costs. The amount of alloying elements added is controlled to within 4%, meeting the requirements for lightweight materials. This invention omits high-temperature, long-duration solution treatment or homogenization processes, shortening the alloy preparation process through direct, rapid hot extrusion. The faster extrusion speed also improves alloy production efficiency, which is beneficial for industrial production. This invention forms small-sized, high-melting-point eutectic phases, uniformly dispersed at grain boundaries and within grains. These phases have good thermal stability and, during hot deformation, can pin grain boundaries, generating highly thermally stable nano-strengthening phases in situ. This promotes segregation and dynamic recrystallization at grain boundaries while effectively inhibiting grain growth, achieving grain refinement and strengthening. In summary, this invention achieves simultaneous improvement of alloy microstructure and enhancement of alloy strength and elongation through the interaction between alloy components, proportions, process, and synergistic control of process parameters, with yield strength ≥253MPa, tensile strength ≥290MPa, and elongation ≥11%. Detailed Implementation

[0011] Example 1

[0012] The alloy is composed of the following components by mass percentage: Bi: 0.5 wt.%, Mn: 0.4 wt.%, Zn: 0.3 wt.%, Al: 0.3 wt.%, with unavoidable impurities ≤ 0.05%, and the balance being Mg; the preparation method includes the following steps:

[0013] (1) According to the alloy composition ratio, under the protection of a mixed gas of CO2 and SF6 with a volume ratio of 97:3, pure magnesium, magnesium-manganese master alloy, pure bismuth, pure zinc and pure aluminum are melted in sequence at 520-660℃. After the alloy is completely melted, it is stirred and slag is removed for 5-10 minutes. Argon gas is introduced and the mixture is kept at a constant temperature for 15-20 minutes to obtain the alloy melt. The alloy melt is then injected into a mold preheated to 150-250℃ using gravity casting to obtain a magnesium alloy ingot.

[0014] (2) The alloy ingot obtained in step (1) is machined to obtain magnesium alloy billet;

[0015] (3) Hot extrusion: The billet and extrusion die obtained in step (2) are preheated at 300°C for 2 hours, and then the billet is extruded at 300°C. The extrusion speed is 4 m / min and the extrusion ratio is 26:1 to obtain a low-cost microalloyed high-performance fast extrusion magnesium alloy with a yield strength of 253 MPa, a tensile strength of 291 MPa and an elongation of 11%.

[0016] Example 2

[0017] The alloy is composed of the following components by mass percentage: Bi: 1.4 wt.%, Mn: 0.6 wt.%, Zn: 0.6 wt.%, Al: 0.4 wt.%, with unavoidable impurities ≤ 0.05%, and the balance being Mg; the preparation method includes the following steps:

[0018] (1) According to the alloy composition ratio, under the protection of a mixed gas of CO2 and SF6 with a volume ratio of 99:1, pure magnesium, magnesium-manganese master alloy, pure bismuth, pure zinc and pure aluminum are melted in sequence at 510-670℃. After the alloy is completely melted, it is stirred and slag is removed for 8-10 minutes. Argon gas is introduced and the mixture is kept at a constant temperature for 15-25 minutes to obtain the alloy melt. The alloy melt is then injected into a mold preheated to 150-250℃ using gravity casting to obtain a magnesium alloy ingot.

[0019] (2) The alloy ingot obtained in step (1) is machined to obtain magnesium alloy billet;

[0020] (3) Hot extrusion: The billet and extrusion die obtained in step (2) are preheated at 310°C for 2 hours, and then the billet is extruded at 310°C. The extrusion speed is 4.5 m / min and the extrusion ratio is 28:1 to obtain a low-cost microalloyed high-performance fast extrusion magnesium alloy. The alloy has a yield strength of 261 MPa, a tensile strength of 294 MPa and an elongation of 14.3%.

[0021] Example 3

[0022] The alloy is composed of the following components by mass percentage: Bi: 2.1 wt.%, Mn: 0.7 wt.%, Zn: 0.6 wt.%, Al: 0.5 wt.%, with unavoidable impurities ≤ 0.05%, and the balance being Mg; the preparation method includes the following steps:

[0023] (1) According to the alloy composition ratio, under the protection of a mixed gas of CO2 and SF6 with a volume ratio of 96:4, pure magnesium, magnesium-manganese master alloy, pure bismuth, pure zinc and pure aluminum are melted in sequence at 500-690℃. After the alloy is completely melted, it is stirred and slag is removed for 8-15 minutes. Argon gas is introduced and the mixture is kept at a constant temperature for 20-25 minutes to obtain the alloy melt. The alloy melt is then injected into a mold preheated to 150-250℃ using gravity casting to obtain a magnesium alloy ingot.

[0024] (2) The alloy ingot obtained in step (1) is machined to obtain magnesium alloy billet;

[0025] (3) Hot extrusion: The billet and extrusion die obtained in step (2) are preheated at 310°C for 3 hours, and then the billet is extruded at 310°C. The extrusion speed is 4.2 m / min and the extrusion ratio is 28:1 to obtain a low-cost microalloyed high-performance fast extrusion magnesium alloy. The alloy has a yield strength of 258 MPa, a tensile strength of 290 MPa and an elongation of 12.2%.

[0026] Comparative Example 1

[0027] A published master's thesis entitled "Influence of Hot Extrusion and Rolling Processes on the Microstructure and Properties of AE44 Magnesium Alloy" mentions in its experiments that the selected AE44 magnesium alloy, by mass percentage, consisted of: Al: 3.99 wt.%, RE(Ce+La): 4.34 wt.%, Mn: 0.36 wt.%, Zn: 0.02 wt.%, Fe: (0.002 wt.%), with the balance being Mg. Before hot extrusion deformation, the alloy underwent homogenization treatment at 450℃ for 12 hours, followed by hot extrusion deformation at an extrusion temperature of 400℃, an extrusion ratio of 16-17:1, and an extrusion exit rate of 2 m / min. The resulting alloy exhibited a room temperature yield strength of 191.2 MPa, a tensile strength of 259.2 MPa, and an elongation of 7.2%. Compared to this invention, Comparative Example 1 underwent a prolonged homogenization treatment, and its extrusion temperature was higher than all embodiments of this invention, while its extrusion speed was lower. This process was complex and unfavorable for industrial production. Meanwhile, the alloy element addition amount in Comparative Example 1 (8.71 wt.%) is significantly higher than the maximum alloy element addition amount in this invention (4 wt.%). Furthermore, Comparative Example 1 contains a large amount of expensive rare earth elements (Ce, La: 4.34 wt.%), with the rare earth element addition amount exceeding the total alloy element addition amount in this invention. In contrast, this invention does not add any rare earth elements, and the selected elements are inexpensive, resulting in lower raw material costs compared to Comparative Example 1. In addition, the highest mechanical properties and plasticity obtained by the alloy in Comparative Example 1 are lower than the lowest mechanical properties and plasticity of the alloy in this invention, respectively. In summary, compared to Comparative Example 1, this invention does not add expensive rare earth elements, has a lower alloy content, simplifies the long-term high-temperature heat treatment steps, allows for lower extrusion temperatures and faster extrusion speeds, and achieves higher mechanical properties and plasticity than Comparative Example 1, realizing a simultaneous improvement in the strength and plasticity of magnesium alloys.

[0028] Comparative Example 2

[0029] The publicly published invention patent entitled "A Preparation Method for Improving the Plastic Forming of Rare Earth Magnesium Alloys" (Application Publication No.: CN112251657A) mentions in its experimental method that the selected Mg-Gd-Er-Zr-X (Al, Ca, Sn) components, by mass percentage, are: Gd: 8-10 wt.%, Er: 0.8-1.5 wt.%, Zr: 0.3-0.7 wt.%, Al: 0-0.2 wt.%, Ca: 0-0.05 wt.%. The alloy, containing 0.2 wt.% Sn and the balance Mg, was first homogenized at 450-475℃ for 4.5-5 hours, followed by hot extrusion at 435-450℃ with an extrusion ratio of 18-20:1 and an extrusion rate of 0.3-0.7 m / min. The extruded alloy was then rolled, resulting in a room temperature yield strength <249 MPa, tensile strength <280.1 MPa, and elongation <6.2%. Compared to this invention, Comparative Example 2 underwent homogenization treatment, and its extrusion temperature was higher than all embodiments of this invention, while its extrusion speed was significantly lower. This resulted in a more complex process, lower production efficiency, and higher energy consumption, which is unfavorable for industrial production. Meanwhile, the amount of alloying elements added in Comparative Example 2 (12.2 wt.%) is far higher than that in this invention (≤4 wt.%). Furthermore, Comparative Example 2 added a large amount of expensive rare earth elements (Gd, Er) (both ≥8.8 wt.%), with the amount of rare earth elements exceeding the total amount added in the alloy obtained in this invention. In contrast, this invention does not add any rare earth elements, and the selected elements are inexpensive, saving costs. Given that the cost of the alloy added in Comparative Example 2 is far higher than that of this invention, and the process used is more complex, the highest mechanical properties and plasticity of the alloy obtained in Comparative Example 2 are lower than the lowest mechanical properties and plasticity of the alloy obtained in this invention. In summary, compared to Comparative Example 2, this invention does not add any rare earth elements, has a lower alloy content, simplifies the long-term high-temperature heat treatment steps, has a lower extrusion temperature and faster extrusion speed, does not employ pre-extrusion heat treatment and post-extrusion rolling processes, has a shorter process flow, and the resulting alloy has higher mechanical properties and plasticity than Comparative Example 2, achieving a simultaneous improvement in the strength and plasticity of the magnesium alloy.

[0030] Compared with existing technologies, this invention does not add rare earth elements and controls the alloy content to ≤4wt.%, resulting in lightweight characteristics. No high-temperature, long-term solution treatment or homogenization heat treatment processes are performed before extrusion, simplifying the production process. It employs a higher extrusion speed than existing technologies. By simplifying the process and through the interaction, proportioning, and synergistic control of the alloy components, process parameters, and other factors, a low-cost, micro-alloyed, high-performance, fast-extruded magnesium alloy is obtained with higher strength and plasticity than existing magnesium alloys containing large amounts of rare earth elements or higher alloy content. Compared with existing technologies, the strength and plasticity of the alloy are simultaneously improved, with a yield strength ≥253MPa, tensile strength ≥290MPa, and elongation ≥11%.

Claims

1. A low-cost, microalloyed, high-performance, rapidly extruded magnesium alloy, characterized in that: The alloy consists of the following components by weight percentage: Bismuth: 0.4-2.2 wt.%, Manganese: 0.3-0.7 wt.%, Zinc: 0.2-0.6 wt.%, Aluminum: 0.2-0.5 wt.%, unavoidable impurities ≤0.05%, balance magnesium; The preparation method of the magnesium alloy includes the following steps: (1) According to the alloy composition ratio, under the protection of a mixed gas of CO2 and SF6 with a volume ratio of 95-99:5-1, pure magnesium, magnesium-manganese master alloy, pure bismuth, pure zinc and pure aluminum are melted in sequence at 500-690℃. After the alloy is completely melted, it is stirred and slag is removed for 5-20 minutes. Argon gas is introduced and the mixture is kept at a constant temperature for 15-30 minutes to obtain the alloy melt. The alloy melt is then injected into a mold preheated to 150-250℃ using gravity casting to obtain a magnesium alloy ingot. (2) The alloy ingot obtained in step (1) is machined to obtain magnesium alloy billet; (3) Hot extrusion: The billet and extrusion die obtained in step (2) are preheated at 300-310℃ for 2-3 hours, and then the billet is extruded at 300-310℃. The extrusion speed is 4-5m / min and the extrusion ratio is 26-30:1 to obtain a low-cost microalloyed high-performance fast extruded magnesium alloy with a yield strength ≥253MPa, tensile strength ≥290MPa and elongation ≥11%.

2. The low-cost microalloyed high-performance rapid extrusion magnesium alloy according to claim 1, characterized in that: The composition, by mass percentage, is bismuth: 0.45-2.1 wt.%, manganese: 0.35-0.65 wt.%, zinc: 0.25-0.55 wt.%, and aluminum: 0.35-0.45 wt.%.

Citation Information

Patent Citations

  • Preparation method for improving plastic forming of rare earth magnesium alloy

    CN112251657A

  • High-speed-extrudable wrought magnesium alloy and preparation method thereof

    CN105154734A

  • Multi-element microalloyed high-efficiency extruded magnesium alloy and preparation method thereof

    CN114540682A